Relationship of chemotherapeutic agents with menstrual disorders in nursing staff - Hashemi, F; Pasyar, N; Dehbashi, S (Advances in Nursing & Midwifery, 2009)
Background Occupational contact with chemotherapeutic drugs is considered as a potential threat for health. These agents may cause menstrual disorders according to many studies regarding the effects of long-term contact of the agents with health personnel. Oncology nurses involved in the preparation and administration of these drugs may be prone to many threats and complications. Purpose This retrospective study was conducted to detect menstrual disorders in nursing staff with or without contact with chemotherapeutic agents at Namazi Hospital in Shiraz. Methods Nurses from chemotherapy, hematology, pediatrics, Eastern 3 as well as bone marrow transplantation wards in case group and from internal general, internal women, internal men as well as Western 3 in control group (totally 94 subjects) was selected. A questionnaire in 4 parts including demographic, past medical history, menstrual disorders and contact with the agents was used for data collection. Pelvic sonography and hormonal tests were also checked. Results 61.1% of nurses in the case group suffered from menstrual disorders in comparison with 53.3% of subjects in the control group. TSH, FSH, and LH levels were higher and prolactin level was lower in the case group. Most nurses in the case group experienced the disorders in the last 6 months. No significant relationship was found between menstrual disorders and application of protective devices. Conclusion Because of potential effects of contact with chemotherapeutic agents on reproductive system, involved staff should use available protective devices to prevent infertility and menstrual disorders. Keywords: Menstrual disorders, Occupational contact, Chemotherapeutic agents.